A medical error: does law help or hinder - Nikitchenko, N. V.; Никитченко, Н. В.; Khankevych, A. M.; Ханькевич, А. М.; Slynko, D. V.; Слинько, Д. В.; Savchuk, T. I.; Савчук, Т. І.; Lazariev, V. V.; Лазарєв, В. В.; Дмитро Слинько; Лазарєв Віктор Вікторович (Wiadomości Lekarskie. - Warsaw, 2019. - Т. LXXII, nr 4. - P. 697-701, 2019)
Системи охорони здоров'я та політика охорони здоров'я в Європейському союзі стають все більш взаємопов'язаними, а також більш складними. Цей взаємозв'язок піднімає багато питань політики охорони здоров'я, включаючи якість охорони здоров'я. Помилки в медичної допомоги можуть виникати в будь-якому місці системи охорони здоров'я - в лікарнях, кабінетах лікарів, будинках для людей похилого віку, аптеках - і в будь-якій частині процесу лікування, пов'язаної з неправильним лікуванням. Метою статті є розробка адекватних теоретичних і науково-практичних пропозицій щодо модернізації правового регулювання для захисту прав пацієнтів, спрямованих на дотримання конституційних прав і свобод.

Introduction: Health systems and health policies across the European Union are becoming more and more interconnected and also more complex. This increased interconnection raises many health policy issues, including health care quality. Mistakes in medical care can occur anywhere in the health care system - at hospitals, doctor's offices, nursing homes, pharmacies, or patients' homes - and in any part of the treatment process involving wrong medication, improper treatment, or incorrect or delayed test results. The aim of the article is to develop adequate theoretical and scientific-practical proposals for the modernization of the legal regulation to protect patients' rights aimed at observance of constitutional rights and freedoms. Patients and methods: Materials and methods: In order to obtain the results the analysis of medical, labor and civil law norms are investigated. The article uses analysis and synthesis methods, as well as a comparative legal method. Results: Review: A number of proposals are given for improving legislation in the area of eliminating obstacles to provision of qualitative primary care / medical-preventive care, prevention of formal attitude towards the patient, the implementation of preventive protection measures which should notify in advance about the violation of the law in the medical sphere. Conclusion: Conclusions: Ukraine urgently needs a legal mechanism to protect the rights of patients; it will become a systemic phenomenon and will consist of legal means, forms, ways by which the restoration of violated patients' rights is provided, the support of protected interests by the law is maintained, legal disputes are resolved and other obstacles to realization of patients' rights are overcome.

Системы здравоохранения и политика здравоохранения в Европейском союзе становятся все более взаимосвязанными, а также более сложными. Эта возросшая взаимосвязь поднимает многие вопросы политики здравоохранения, включая качество здравоохранения. Ошибки в медицинской помощи могут возникать в любом месте системы здравоохранения - в больницах, кабинетах врачей, домах престарелых, аптеках - и в любой части процесса лечения, связанной с неправильным лечением. Целью статьи является разработка адекватных теоретических и научно-практических предложений по модернизации правового регулирования для защиты прав пациентов, направленных на соблюдение конституционных прав и свобод.
Keywords: publikatsii u Scopus; publikatsii u zarubizhnomu vydanni; patients’ rights; responsibility; protection of patients’ rights and interests; medical law; права пациентов; ответственность; защита прав и интересов пациентов; медицинское право; права пацієнтів; відповідальність; захист прав та інтересів пацієнтів; медичне право; medical error; лікарська помилка; медицинская ошибка; Європейський Союз; Европейский Союз; Конституційне право. Constitutional Law. Конституционное право; Наукові публікації. Scientific publications. Научные публикации